TERAPI BERKALA KOMBINASI BIMBINGAN KONSELING ISLAM DENGAN RATIONAL EMOTIF BEHAVIOR THERAPHY (REBT) PADA PENANGANAN PERILAKU AGRESIF ANAK DI SD AL-FALAH ASSALAM TROPODO SIDOARJO - Lukman Fahmi Fahmi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2019)
Abstract: In this study, researchers will examine psychological therapy methods in handling the aggressive attitude of a 4th grade elementary school student at SD Al-Falah Assalam Tropodo Sidoarjo through the RATIONAL EMOTIVE BEHAVIOR THERAPHY (REBT) approach. REBT is a therapeutic method that was initiated by an American psychologist, Albert Ellis in the 1950s. This REBT therapy method focuses on improving attitudes or behaviors, where the individual's behavior is caused by 2 main factors; Internal factors related to genes and external factors related to the environment the individual lived. For this research method, researchers used a qualitative descriptive approach, in which the research subjects were elementary school students grade 4 who were identified as having an aggressive attitude. This research is intended to find information, about the students' aggressive attitudes and then look for information related to what factors influence the aggressive behavior. Furthermore, applying the REBT method in dealing with the aggressive attitude, as well as to determine the effectiveness of the REBT method in handling the child's aggressive attitude. Researchers hope this research can be used as a reference in dealing with the aggressive behavior of other students.Keywords: Aggressive Behavior, REBT, A-B-C Theory